Bizarre tRNAs inferred from DNA sequences of mitochondrial genomes of nematode worms. - Wolstenholme, D R (1987)
The complete nucleotide sequence of the mitochondrial DNA (mtDNA) molecule of the parasitic nematode worm Ascaris suum has been determined. This molecule lacks genes for tRNAs of the standard form. Instead, 21 sequences are found that can be folded into structures that resemble tRNAs in which the T psi C arm and variable loop are missing and replaced with a single loop of between 4 and 12 nucleotides. Considerations of various properties of these sequences, including the number, predicted anticodons, conserved nucleotides, direction of transcription, base composition, and relative gene arrangements are consistent with the interpretation that they are genes for a different sort of tRNA. Transfer RNA genes with a similar potential secondary structure are found in mtDNA of the free-living nematode Caenorhabditis elegans, suggesting that this unusual form of tRNA is used by all nematode mitochondria.